Infecciones urinarias adquiridas en la comunidad: epidemiología, resistencia a los antimicrobianos y opciones terapéuticas - Guevara P Armando; Machado B Sara; Manrique T Esther (Kasmera, 2011)
Abstract> Urinary tract infections (UTI) are one of the main reasons for consultation in primary care. In recent years, there have been substantial changes in susceptibility patterns for major urinary tract pathogens, which have conditioned changes in their empirical treatment. The aim of this study was to characterize UTI in patients from the community. The sample consisted of 71 patients of both sexes over 18 years of age. The most affected sex was the female (80.28%). The signs and symptoms were lumbar pain, dysuria and abdominal pain. The presence of kidney stones was the most important predisposing factor (39.43%), followed by menopause (23.94%); 63.38% of the patients had a previous UTI. Escherichia coli was the most common agent (63.89%), followed by Proteus mirabilis (6.94%). Isolates showed high levels of resistance to ampicillin, cephalothin and norfloxacin. 51.52% of the Enterobacteriaceae were resistant to fluoroquinolones and 16.67% showed production of extended spectrum B-lactamases (ESBL). Most of the agents were susceptible to nitrofurantoin, regardless of the presence of resistance mechanisms affecting other antibiotic groups.